2017
DOI: 10.1007/s12551-017-0263-9
|View full text |Cite
|
Sign up to set email alerts
|

Tampering with springs: phosphorylation of titin affecting the mechanical function of cardiomyocytes

Abstract: Reversible post-translational modifications of various cardiac proteins regulate the mechanical properties of the cardiomyocytes and thus modulate the contractile performance of the heart. The giant protein titin forms a continuous filament network in the sarcomeres of striated muscle cells, where it determines passive tension development and modulates active contraction. These mechanical properties of titin are altered through post-translational modifications, particularly phosphorylation. Titin contains hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
63
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 99 publications
3
63
0
6
Order By: Relevance
“…For instance, phosphorylation of the cardiac N2B region increases the persistence length of the elastic titin spring, which results in reduced overall titin-based stiffness and force. By contrast, phosphorylation of the PEVK region reduces the effective free spring length yielding increased stretch-dependent stiffness and force [76]. Hence, it is expected that titin makes a complex contribution to several phases of the cardiac cycle.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, phosphorylation of the cardiac N2B region increases the persistence length of the elastic titin spring, which results in reduced overall titin-based stiffness and force. By contrast, phosphorylation of the PEVK region reduces the effective free spring length yielding increased stretch-dependent stiffness and force [76]. Hence, it is expected that titin makes a complex contribution to several phases of the cardiac cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Levels of N2BA and N2B in the heart are regulated by splicing factors (Labeit & Kolmerer, 1995;Freiburg et al 2000;Bang et al 2001). Another mechanism to decrease passive stiffness is increasing protein kinase A/protein kinase G/extracellular signal-regulated kinase 2 phosphorylation or decreasing protein kinase C phosphorylation (Hamdani et al 2017). The in vivo consequences of decreasing titin stiffness have been extensively studied since the finding from Greaser et al (2008) who identified a rat model that expressed a large highly compliant isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Нормальное соотношение N2BA и N2B в миокарде человека составляет примерно 30:70 [19]. Это соотношение регулируется протеинкиназами А и G, а также кальцийкальмодулинкиназой (CaMKII), снижающими упругость титина [20], и протеинфосфатазами, осуществляющими дефосфорилирование и повышающими его упругость. Дефосфорилирование титина происходит при ограни-чении ресинтеза АТФ, в результате повышаются упругость миофибрилл и диастолическая упругость миокарда в целом.…”
Section: Discussionunclassified
“…Дефосфорилирование титина происходит при ограни-чении ресинтеза АТФ, в результате повышаются упругость миофибрилл и диастолическая упругость миокарда в целом. Сниженное отношение N2BA:N2B представляет общий признак ХСН у людей с сохраненной ФИ [19,20]. Упругость титина может также возрастать при действии активных форм кислорода, когда в молекуле титина образуются дисульфидные связи, они разрушаются при глутатионилировании [20].…”
Section: Discussionunclassified